The profile of propanolol HCl release from sustained release tablet with floating system used matrix Methocel K15M - T. N. Saifullah; Yandi Syukri; Rini Utami (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
The aim of this research was to study the profile of propanolol HCl release from sustained release tablet with a floating system using matrix Methocel K15M. Citric acid and sodium bicarbonate were used as gasgenerating agents. Tablets were made by wet granulation method in four formulations based on the variation concentration of Methocel K15M. The concentrations were 90 mg/tablet (F1), 105 mg/tablet (F2), 120 mg/tablet (F3) and 135 mg/tablet (F4) respectively. The produced tablets were tested for physical characteristics such as uniformity of weight, tablet hardness, drug concentration, floating test and the dissolution. In the dissolution testing used Becker method in HCl pH 3.0 as medium dissolution at 37±0.50 C; with a speed 50 rpm during five hours. The results of dissolution showed that the release profile of propanolol HCl following zero order kinetic that showed amount of propanolol HCl were released linear with time. Mechanisms of propanolol HCl release were combination of diffusion and erosion, however diffusion more dominant. Rate of release (k value) of drugs were 0.174 %/minute (FI); 0.101 %/minute (FII); 0.105 %/minute (FIII); and 0.108 %/minute (FIV).Key words: Propanolol HCl, Floating, Methocel K15M